The impact of the awarding of state tenders and quotations on black economic empowerment in the Free State Province in the 2000-2006 financial years - Mohokare, Sesheme Meshack (University of the Free State, 2008)
The first democratic government of South Africa that was inaugurated into office in 1994, inherited a society that was divided between the haves and the have nots. The haves were mainly whites who benefited economically under the National Party led government. The have nots were mainly blacks who were in the majority. The blacks were not allowed to participate in the economy of South Africa. The task that faces the new democratic government is to redress the wrong-doings of the past. The democratic government is faced with the challenge of improving the lives of the blacks politically, economically and socially. The democratic government did not hesitate to make its intentions clear of redressing the imbalances of the past. The votes of the electorate who voted the new government into office, were interpreted by the politicians as a mandate to redress the wrongs committed by the National Party government. The government engaged in rigorous policy making processes and new policies were passed in both the national and provincial governments. The government is faced with a number of challenges. When the current government took over, the number of blacks participating in the economy was very small. The current government is faced with the challenge of increasing the number of blacks participating in the mainstream economy of the country. In order to bring in more blacks into the mainstream economy, the state had to channel state tenders to blacks. The debate that is going on is on the successes and the failures of the government both national, provincial and local in bringing blacks into the mainstream economy through the channeling of state tenders. Much has been said about factors that have had a negative and positive impact on black economic empowerment. This dissertation is a study of the impact of tenders awarded to blacks by the Free State Provincial Government on black economic empowerment. The focus in the dissertation will be on whether the Free State Government is actually succeeding in empowering the blacks economically. In this rubric, the following will be outlined: Background and reasons for the study, problem statement, hypothesis formulation, objective of the research, research methodology, key words and concepts and the scope of the dissertation.
Dissertation(M.P.A.(Public Administration))--University of the Free State, 2008
Keywords: Blacks and designated groups; Economy; Fair discrimination; Targets; Scorecard; Efficiency; Effectiveness; Corruption; Sustainability; Tenders; Outsourcing; Black Economic Empowerment